2019
DOI: 10.3310/phr07200
|View full text |Cite
|
Sign up to set email alerts
|

Individual health trainers to support health and well-being for people under community supervision in the criminal justice system: the STRENGTHEN pilot RCT

Abstract: Background Little is known about the effectiveness or cost-effectiveness of interventions, such as health trainer support, to improve the health and well-being of people recently released from prison or serving a community sentence, because of the challenges in recruiting participants and following them up. Objectives This pilot trial aimed to assess the acceptability and feasibility of the trial methods and intervention (and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The reported increased changes illustrate the potential for improvements in public health. Yet we find that only five studies at the individual level [ 27 , 57 , 60 , 79 , 81 ], two studies at the system level [ 60 , 79 ], and two studies at the community level [ 27 , 79 ] provide evidence to support claims that the observed change is due to a particular social prescribing programme. Given this small number of studies that establish causality, conclusions regarding the impact of social prescribing are tentative, at best.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…The reported increased changes illustrate the potential for improvements in public health. Yet we find that only five studies at the individual level [ 27 , 57 , 60 , 79 , 81 ], two studies at the system level [ 60 , 79 ], and two studies at the community level [ 27 , 79 ] provide evidence to support claims that the observed change is due to a particular social prescribing programme. Given this small number of studies that establish causality, conclusions regarding the impact of social prescribing are tentative, at best.…”
Section: Discussionmentioning
confidence: 62%
“…Thirty-six studies employ a pre/post design [ 26 , 27 , 37 , 38 , 39 , 44 , 55 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], 8 report case studies with evidence taken at one point in time [ 26 , 42 , 70 , 74 , 78 , 83 , 85 , 86 ], 16 studies conduct surveys [ 27 , 37 , 55 , 57 , 58 , 60 , 62 , 63 , 68 , 72 , 77 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations